How Green is Green Islam? Religious Environmentalism and Public Policy in Indonesia - Wijsen, Frans (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
Studies of religious environmentalism often start from the assumption that religious communities are essential to the fight against environmental changes. In this article I will address the question whether and in what way this is indeed the case, and if and how religious environmental ethics can be integrated into public policy. Numerous large-scale studies show that evidence for a relationship between religious beliefs and environment-friendly behavior is not robust. Integrating religious beliefs into public policy is not unambiguous. This article has two parts. In the first part I draw on the religious environmentalism actions study and the humans and nature study to explore empirical evidence for a relationship between religious beliefs and environmental ethics in Indonesia. In the second part I ask what this evidence signifies for environmental policy making. I advocate a discursive approach in policy-making showing the multiplicity of meanings of environmental problems and the need of forming discourse coalitions.